Influence of Media Leaflets on the Mother's Behaviour on the Language Development of the Child - Sari, Fitria Dila; Deswita, Deswita; Fajria, Lili (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Language development is vital in toddlerhood. In Indonesia, language and speech delays in children aged 36–48 months range from 5–10%.Objective: This study aims to see the effect of leaflet media on the knowledge and attitudes of mothers.Method: This quantitative research uses the research design "Quasy Experimental Pre-Post Test With Control Group". The population in the study was all mothers with children aged 36–48 months in the Lubuk Buaya Padang Health Center working area in 2023, with a total population of 955. There were 30 samples, consisting of 15 intervention groups and 15 control groups. The sampling method used is non-probability sampling, namely, consecutive sampling.Result: The results of this study showed that there was a significant influence after being given leaflet media interventions to mothers on changes in knowledge (p = 0.002) and attitudes (p = 0.008), while the p-value of the control group for knowledge variables (p = 0.001) and attitudes (p = 0.056).Conclusion: It is hoped that nurses at the Public Health Center can educate mothers about stimulation and early detection of language development in children aged 36-48 months, and mothers are expected to be able to spare or provide their time to read the leaflets that have been given and repeat them to understand the contents and carry out all forms of stimulation and early detection of language development in children according to what is stated in the leaflet